2016
DOI: 10.1007/s11060-016-2065-5
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab and temozolomide versus temozolomide alone as neoadjuvant treatment in unresected glioblastoma: the GENOM 009 randomized phase II trial

Abstract: We sought to determine the impact of bevacizumab on reduction of tumor size prior to chemoradiotherapy in unresected glioblastoma patients. Patients were randomized 1:1 to receive temozolomide (TMZ arm) or temozolomide plus bevacizumab (TMZ + BEV arm). In both arms, neoadjuvant treatment was temozolomide (85 mg/m(2), days 1-21, two 28-day cycles), concurrent radiation plus temozolomide, and six cycles of adjuvant temozolomide. In the TMZ + BEV arm, bevacizumab (10 mg/kg) was added on days 1 and 15 of each neoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…A random-effects model was used to pool the OS data. 10 , 11 , 13 15 The pooled data showed that a BEV agent plus chemotherapy did not improve the OS (HR =0.91, 95% CI =0.76–1.08, P =0.28) than the control treatment ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…A random-effects model was used to pool the OS data. 10 , 11 , 13 15 The pooled data showed that a BEV agent plus chemotherapy did not improve the OS (HR =0.91, 95% CI =0.76–1.08, P =0.28) than the control treatment ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 98%
“…Based on the criteria described in the “Methods” section, 10 publications were evaluated in more detail, but some did not provide enough detail of the outcomes of two approaches. Therefore, we had a final total of six RCTs 10 15 assessing the value of BEV in patients with newly diagnosed GB. The search process is described in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results reconfirmed the potential benefit of combined TMZ, BEV, and CK-SRT. A recent study by Balana et al compared BEV-plus-TMZ to TMZ alone, enrolling 102 patients [ 7 ]. The authors showed that PFS and OS were longer in the TMZ + BEV arm, although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%